Poor Cognitive Outcome in Shunt-Responsive Idiopathic Normal Pressure Hydrocephalus - Koivisto, Anne M.; Alafuzoff, Irina; Savolainen, Sakari; Sutela, Anna; Rummukainen, Jaana; Kurki, Mitja; Jääskeläinen, Juha E.; Soininen, Hilkka; Rinne, Jaakko; Leinonen, Ville (Neurosurgery, 2013)
Abstract BACKGROUND: Idiopathic normal pressure hydrocephalus (iNPH) causes cognitive decline that can be alleviated by shunting, but long-term outcome studies are scarce. OBJECTIVE: To elucidate the long-term cognitive condition of shunt-responsive iNPH patients. METHODS: The follow-up data (Kuopio University Hospital NPH Registry) of 146 patients diagnosed with iNPH by clinical and radiological examination, 24-hour intraventricular pressure monitoring, frontal cortical biopsy, and response to the shunt were analyzed for signs of dementia. The Diagnostic and Statistical Manual for Mental Disorders, Fourth Edition, and specified memory disorder criteria were used. Median follow-up was 4.8 years. RESULTS: At the end of follow-up, 117 (80%) of the 146 iNPH patients had cognitive decline and 67 (46%) had clinical dementia. The most common clinical diagnoses were Alzheimer disease and vascular dementia. In multivariate analysis of the 146 iNPH patients, memory deficit as a first symptom before shunt (odds ratio [OR] 18.3; 95% confidence interval [CI] 1.9–175), male sex (OR 3.29; 95% CI 1.11-9.73), age (OR 1.17 year; 95% CI 1.07-1.28), and follow-up time (OR 1.20 year; 95% CI 1.02-1.40) predicted dementia. Interestingly, 8 (5%) iNPH patients had dementia without any signs of other neurodegenerative diseases in clinical, neuroradiological, or brain biopsy evaluation. These patients initially presented a full triad of symptoms, with gait disturbance being the most frequent initial symptom followed by deterioration in cognition. CONCLUSION: The novel findings were (a) a significant risk of dementia in iNPH initially responsive to cerebrospinal fluid shunt, (b) cognitive impairment most commonly due to iNPH-related dementia followed by concurrent degenerative brain disease, and (c) a subgroup with dementia related to iNPH without comorbidities.